The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.3311/ppci.9700
|View full text |Cite
|
Sign up to set email alerts
|

Stress Analysis of Segmental Tunnel Lining Using Artificial Neural Network

Abstract: The paper describes an artificial neural network method (ANNM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Rastbood et al applied MLP to predict yield stresses and displacement of segmental tunnel lining rings based on the results obtained from the numerical method [12]. It is concluded that among all input variables, height is the most effective parameters on outputs parameters.…”
Section: G Other Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rastbood et al applied MLP to predict yield stresses and displacement of segmental tunnel lining rings based on the results obtained from the numerical method [12]. It is concluded that among all input variables, height is the most effective parameters on outputs parameters.…”
Section: G Other Applicationsmentioning
confidence: 99%
“…Mahdevari et al estimated the unknown nonlinear relationship between the rock parameters and tunnel convergence by using the data from the Ghomroud water conveyance tunnel in Iran [11]. Rastbood et al developed an ANN to predict the stresses executed on segmental tunnel lining [12]. Wu et al applied ANN to verify the proposed tunnel ventilation system with variable jet speed [13].…”
Section: Introductionmentioning
confidence: 99%
“…to identify the in uence of each input variable on the output parameters [39]. By analyzing the time history of the software Plaxis 2D, it was determined that the acceleration history of the key points of the model was dependent on the soil mechanical parameters such as friction angle (φ), cohesion (C), dilation angle (ψ), soil unit weight (c), and Poisson's ratio (υ).…”
Section: Sensitivity Analysis Sensitivity Analysis Was Performedmentioning
confidence: 99%
“…Neural network is not new in machine learning, but it has been widely used for various applications over the last two decades thanks to the tremendous improvement in computational technology and innovative data mining algorithms. More and more researchers have interest in applying neural network on civil engineering problem, such as tunneling settlement (Ocak and Seker, 2013), building damage (Moosazadeh et al, 2019), structural forces (Rastbooda et al, 2017). Analysis of pressure grouting has been carried out with neural network which give enlightening results (Zettler et al, 1997).…”
Section: Neural Networkmentioning
confidence: 99%
“…The solutions of governing equation for the aquifer are derived using diverse methods in which there are exact solutions and approximations. The exact solutions utilize complex variable method (Fang et al, 2015;Fattah et al, 2010;Kolymbas and Wagner, 2007) and mirror image method (Li et al, 2018b;Rastbooda et al, 2017), and approximation applies axisymmetric modelling method (Goodman et al, 1964;Hwang and Lu, 2007), as shown in Figure 3.2. In the complex variable method (CVM), the semi-infinite aquifer is mapped conformally to two circles with the same centre in polar coordinate.…”
Section: Solutions Derivation For Water Inflow In Aquifermentioning
confidence: 99%